Sunlight-Induced Photochemical Degradation of Methylene Blue by Water-Soluble Carbon Nanorods - Anshu Bhati; Anupriya Singh; Kumud Malika Tripathi; Sumit Kumar Sonkar (International Journal of Photoenergy)
Water-soluble graphitic hollow carbon nanorods (wsCNRs) are exploited for their light-driven photochemical activities under outdoor sunlight. wsCNRs were synthesized by a simple pyrolysis method from castor seed oil, without using any metal catalyst or template. wsCNRs exhibited the light-induced photochemical degradation of methylene blue used as a model pollutant by the generation of singlet oxygen species. Herein, we described a possible degradation mechanism of methylene blue under the irradiation of visible photons via the singlet oxygen-superoxide anion pathway.